The Implikasi dan Strategi Teori Elastisitas Permintaan dalam Ekonomi Manajerial - Suriyanti; Ayi Nurpadilah, Ayi Nurpadilah; Hasan, Dina Nurmala; Fauziah, Hesti; Octaviani, Lidiyana Tasya; amelia, Fannisya (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
This article will discuss the factors influencing demand elasticity, the methods of measuring it, and the implications and strategies companies can apply based on this concept. The main factors affecting demand elasticity include the availability of substitute goods, the proportion of income spent on the good, and the time frame given to respond to price changes. The more alternatives available to consumers, the more elastic the demand for a good becomes. A deep understanding of demand elasticity enables companies to make smarter pricing decisions. Companies can maximize revenue and market share by considering the factors influencing elasticity and analyzing market conditions. This elasticity analysis helps identify market segments responsive to price changes to develop effective marketing strategies. Besides price, product quality, brand image, and customer service also affect demand. Integrating these factors into pricing decisions helps companies remain competitive and adaptive.